2009
DOI: 10.1159/000200017
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Fetoscopic Laser Decompression of Congenital High Airway Obstruction Syndrome (CHAOS) from Laryngeal Atresia via a Single Trocar – Current Technical Constraints and Potential Solutions for Future Interventions

Abstract: Objective: To alleviate congenital high airway obstruction syndrome (CHAOS) from laryngeal atresia by percutaneous minimally-invasive fetoscopic tracheal decompression using laser. Methods: The procedure was performed via one trocar under general maternofetal anesthesia in a human fetus with CHAOS from laryngeal atresia at 21+6 weeks of gestation. Results: Normalization of the lung-heart size relationship was observed within days after the procedure. The fetus was delivered by ex utero intrapartum treatment (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 16 publications
(7 reference statements)
0
33
0
1
Order By: Relevance
“…Only six attempts of fetal therapy for CHAOS have been reported [5,6,7,8,14]. In the first case, Ward et al [5] attempted an open surgery fetal tracheostomy at 18 weeks' gestation, but there was a fetal death a few hours later.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only six attempts of fetal therapy for CHAOS have been reported [5,6,7,8,14]. In the first case, Ward et al [5] attempted an open surgery fetal tracheostomy at 18 weeks' gestation, but there was a fetal death a few hours later.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, diaphragmatic function remained impaired so that tracheotomy and ventilatory support were continued beyond discharge from hospital at 4 months of age. The infant died at home 2 weeks later [8]. Finally, Saadai et al [14] reported 2 cases which underwent fetal bronchoscopy with an attempted wire tracheoplasty, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations